A policy framework including trust and reputation in grid environments - Stefan König; Raimund Matros; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2007)
This paper examines the role of policies in different grid environments. A Grid technology becomes standardized and stable, various business models are envented and increasingly applied, and economic implications can be observed.Asymmetrically distributed information may allow for opportunistic behaviour of service providers or users who exploit the information gap between providers and consumers on the quality of services.
urn:nbn:de:bvb:703-opus-4486
Keywords: 330; Grid Computing